2014
DOI: 10.1310/tsr2105-443
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Research Staff’s Experiences of Seeking Consent from People with Communication Difficulties: Results of a National Online Survey

Abstract: For research staff to work more effectively with this population, study protocols need to be more inclusive of people with communication difficulties, and staff need better access to ethically approved, accessible communication resources and appropriate training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…The lack of training and resources has been identified as potential reasons for inappropriate capacity assessment, which leads to the exclusion of PWA from clinical and research studies, even by specialist staff, such as stroke research staff (Jayes & Palmer, 2014). Jayes and Palmer (2014) found that only 18% of 75 stroke research staff used accessible information when obtaining consent from PWA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of training and resources has been identified as potential reasons for inappropriate capacity assessment, which leads to the exclusion of PWA from clinical and research studies, even by specialist staff, such as stroke research staff (Jayes & Palmer, 2014). Jayes and Palmer (2014) found that only 18% of 75 stroke research staff used accessible information when obtaining consent from PWA.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of training and resources has been identified as potential reasons for inappropriate capacity assessment, which leads to the exclusion of PWA from clinical and research studies, even by specialist staff, such as stroke research staff (Jayes & Palmer, 2014). Jayes and Palmer (2014) found that only 18% of 75 stroke research staff used accessible information when obtaining consent from PWA. Rowland and McDonald (2009) found that capacity assessors lacked the skills as effective communicators and were unable to modify the process to support communication, which led to incorrect conclusions about capacity for decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…An outcome of this refinement was that the people with aphasia who took part reported increased confidence in communicating and felt stimulated and empowered to improve future services for those with similar difficulties. However, although there have been some positive outcomes [23], few study protocols and research include people with aphasia, despite the potential patient and service gains [23,24]. Failure to include this population in stroke research poses the question of the generalisability of research findings to stroke survivors with communication difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Determining whether the individual can demonstrate capacity for a specific decision, at a specific time is critical to striking the balance between respecting patient autonomy and acting in a patient's best interest. Communication disorders, such as aphasia, present challenges for assessing DMC (Ferguson, Duffield, & Worrall, 2010;Jayes & Palmer, 2014;Shames, 2012;Suleman & Hopper, 2016;Zuscak, Peisah, & Ferguson, 2015). A skilled capacity assessment for people with aphasia by health-and social-care professionals will improve care outcomes and ensure that the principles of patient-centred care are upheld.…”
mentioning
confidence: 99%
“…In such situations, provision should be made to ensure the individual's communication needs are meet using simple language, visual aids or any other means suitable for that particular patient. In the context of communication difficulties experienced by people with aphasia, the accuracy and reliability of DMC assessments often remain questionable, especially when conducted by untrained or less optimally trained professionals, and by those professionals who are unfamiliar with aphasia (Carling-Rowland, Black, McDonald, & Kagan, 2014;Ferguson et al, 2010;Jayes & Palmer, 2014;Suleman & Hopper, 2016). It is not surprising that studies have found that people with aphasia were presumed to lack capacity due to their communication difficulties (Carling-Rowland & Wahl, 2010;Pachet, Allan, & Erskine, 2012).…”
mentioning
confidence: 99%